2022
DOI: 10.1055/s-0041-1740222
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dental Anxiety and Hemodynamic Changes during Different Dental Procedures: A Report from Eastern Saudi Arabia

Abstract: Objectives This study aimed to investigate hemodynamic changes in healthy adult patients during different dental procedures and evaluate whether these changes were associated with patients' dental anxiety. Materials and Methods A convenience sample of 119 patients of both genders undergoing routine dental care participated in the study. Participants responded to the Arabic version of the modified dental anxiety scale (MDAS) and a self-structured questionnaire. Each patient had their blood pressure, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The lack of statistical significance in the other comparisons may indicate that these dental characteristics are not major predictors of anxiety in the study population. These findings are consistent with a previous study that found patients who have visited a dentist before have less anxiety than those who have not and that those who have had a bad dental experience have higher levels of anxiety [ 32 ]. In contrast, other reports found no significant association between previous dental visits and dental anxiety [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The lack of statistical significance in the other comparisons may indicate that these dental characteristics are not major predictors of anxiety in the study population. These findings are consistent with a previous study that found patients who have visited a dentist before have less anxiety than those who have not and that those who have had a bad dental experience have higher levels of anxiety [ 32 ]. In contrast, other reports found no significant association between previous dental visits and dental anxiety [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, the injection itself can be a significant source of anxiety for patients. The fear of needles and injections is common, and patients may worry about the pain and discomfort associated with the injection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, instead of asking the question “How would you feel if you were to go to the dentist tomorrow?” the scale begins with the question “How do you feel when you embark on the journey of treatment?” Responses given in a more comfortable environment away from dental clinic settings and in different states of mind may differ from those given while sitting in the dentist’s chair [ 3 , 43 ]. According to a study by Alghareeb et al, 42.9% of participants showed very low levels of anxiety in response to the first question of the MDAS [ 44 ]. For example, individuals who complete the MDAS survey just before undergoing treatment may not respond to the first question in the same way as they would in the comfort of their own home.…”
Section: Discussionmentioning
confidence: 99%
“…Not only rotating instruments but also non-rotating and noiseless hand instruments can be among the causes of dental fear. According to literature [ 44 ], extraction is one of the most feared procedures and results in higher levels of dental anxiety compared to other procedures such as restoration, root canal treatment, and periodontal scaling. Therefore, a question has been prepared to measure the level of dental fear that may arise due to noiseless hand instruments.…”
Section: Discussionmentioning
confidence: 99%